Analisis Technology Acceptance Model Dan Persepsi Risiko Terhadap Minat Bertransaksi Mobile Banking Nasabah Bank Syariah Indonesia di Kota Jambi - Resi Putri Anggraini; Novi Mubyarto; Addiarrahman Addiarrahman (Jurnal Ilmiah Ekonomi Islam, 2023)
This thesis aims to know the effect of analysis of technology acceptance model and risk perception on interest in transacting using mobile banking on Indonesian Sharia Bank (BSI) customers branch Gatot Subroto Jambi. This research includes causal associative research. This type of research is a quantitative research. Where the data collection techniques in the form of primary and secondary data. The collection of data obtained is by means of a questionnaire. The sample in this study amounted to 100 people. The analysis used is multiple linear regression analysis with the help of SPSS. Several stages of the test are carried out consisting of validity, reliability, classical assumption test, T test, F test and the coefficient of determination test. Based on the results of the F (simultaneous) test, the Fcount value of 44.386 > Ftabel 2,31 and a significant value of 0.000